2019
DOI: 10.3892/mmr.2019.10755
|View full text |Cite
|
Sign up to set email alerts
|

Theaflavin attenuates cerebral ischemia/reperfusion injury by abolishing miRNA‑128‑3p‑mediated Nrf2 inhibition and reducing oxidative stress

Abstract: Theaflavin has been proven to own strong antioxidative capacity; however, the molecular mechanism underlying its protective effect against cerebral ischemia-reperfusion (I/R) injury remains unclear. Therefore, the present study was designed to elucidate the neuroprotective effects of theaflavin on cerebral I/R injury and its underlying molecular mechanisms. To investigate the effects of theaflavin on neurological function, neurogenesis, and oxidative stress, experiments were performed using a cerebral I/R inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…Among polyphenols, catechins are the main ones in green tea, while the black tea contains theaflavins [ 27 ]. Li et al evidenced that theaflavin (C 29 H 24 O 12 ; CAS number 4670-05-7; Figure 1 (1)) exerted beneficial effects both in in vivo and in vitro models of I/R abolishing miRNA-128-3p-induced Nrf2 suppression and thus decreasing oxidative stress [ 28 ]. In particular, in rats subjected to MCAO, theaflavin administration lowered infarct volume and neuronal damage, and ameliorated neurological abilities.…”
Section: Natural Compounds As Modulator Of Nrf2 Pathway In Stroke mentioning
confidence: 99%
See 1 more Smart Citation
“…Among polyphenols, catechins are the main ones in green tea, while the black tea contains theaflavins [ 27 ]. Li et al evidenced that theaflavin (C 29 H 24 O 12 ; CAS number 4670-05-7; Figure 1 (1)) exerted beneficial effects both in in vivo and in vitro models of I/R abolishing miRNA-128-3p-induced Nrf2 suppression and thus decreasing oxidative stress [ 28 ]. In particular, in rats subjected to MCAO, theaflavin administration lowered infarct volume and neuronal damage, and ameliorated neurological abilities.…”
Section: Natural Compounds As Modulator Of Nrf2 Pathway In Stroke mentioning
confidence: 99%
“…These enzymes have an important role in counteracting oxidative stress: SOD catalyzes the reaction of dismutation of the superoxide radical leading to the formation of O 2 and hydrogen peroxide (H 2 O 2 ), while GPx eliminates H 2 O 2 forming water and O 2 , through the oxidation of glutathione (GSH). The antioxidant effects of theaflavin may be due to its capacity to increase dose-dependently Nrf2 expression reducing miRNA-128-3p levels in vivo and in vitro [ 28 ]. It is important to mention that MDA shows some limits in order to be considered as a marker of oxidative stress.…”
Section: Natural Compounds As Modulator Of Nrf2 Pathway In Stroke mentioning
confidence: 99%
“…Theaflavin as a neuroprotective agent declined the I/R‐induced upregulation of miRNA‐128‐3p, whereas it upgraded Nrf2 protein level in an animal model of stroke. Theaflavin ameliorated oxidative stress and potentiated learning and memory in the MCAO rat model (R. Li et al, 2019). miR‐134 is the next downregulated miRNA in the MCAO mice's peri‐infarct area (C. Liu et al, 2012).…”
Section: Neurological Disorders Associated With Cognitive Impairmentmentioning
confidence: 99%
“…Liang et al found that miRNA-320 promotes cerebral I/R injury in mice by inhibiting IGF-1 expression [20]. Similarly, miRNA-128-3p promotes cell proliferation by regulating Nrf2, which inhibits cell apoptosis and alleviates oxidative stress [21]. miRNA-128-3p also has a protective effect against cerebral I/R injury.…”
Section: Introductionmentioning
confidence: 99%